2011
DOI: 10.1111/j.1365-2265.2010.03918.x
|View full text |Cite
|
Sign up to set email alerts
|

Foetal and postnatal growth and bone mass at 6 months: the Generation R Study

Abstract: Our findings suggest that growth patterns in foetal and postnatal life are associated with bone mass in infancy and may have consequences for bone mass in later life. Follow-up studies are needed to assess whether and to what extent maternal anthropometrics, foetal and postnatal growth patterns have an effect on bone status in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 59 publications
(141 reference statements)
0
28
2
Order By: Relevance
“…The association of birth weight with bone mineral density and content at different ages is conflicting; some studies have shown positive associations between birth weight and bone mineral density (BMD) in pre-pubertal individuals [14,15]. Similarly, positive associations have been observed between birth weight and bone mineral content (BMC) in young adults, postmenopausal women and elderly [16,17].…”
Section: Introductionmentioning
confidence: 96%
“…The association of birth weight with bone mineral density and content at different ages is conflicting; some studies have shown positive associations between birth weight and bone mineral density (BMD) in pre-pubertal individuals [14,15]. Similarly, positive associations have been observed between birth weight and bone mineral content (BMC) in young adults, postmenopausal women and elderly [16,17].…”
Section: Introductionmentioning
confidence: 96%
“…In the second study, growth in FL and AC between the 11th and 19th weeks of pregnancy was positively associated with bone area and BMC at birth and 4 years of age 34. In the Generation R Study,35 second and third trimester EFW were positively associated with bone mineral density (BMD) and BMC in 6-month-olds; some associations were only present for either lumbar spine only or total body BMD and BMC. Change in EFW between 20 and 30 weeks, but not between 30 weeks and term, was also positively associated with BMD for total body.…”
Section: Resultsmentioning
confidence: 93%
“…One of the studies achieved a strong global rating,15 12 received a moderate rating (most failed to gain strong rating by not demonstrating how non-participation affected the population demographics) and the remainder were given a weak rating (most failed to gain moderate rating by not demonstrating whether/how confounders such as maternal smoking and socioeconomic status were considered), see online data supplementary table E2. Of the 6 studies which found no evidence of association between small fetal size and postnatal outcome, 4 were of poor quality study design23 26 35 and 2 of moderate quality 17 31. Among the 4 studies which found no association between changing fetal size and outcomes, 3 were of moderate quality design21 24 31 and the fourth of poor quality 32…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these findings have been supported by studies from birth cohorts elsewhere. In Generation R, a mother‐offspring cohort in Rotterdam, Netherlands, fetal weight gain and catch‐up in weight were associated with BMD at the whole‐body site at 6 months . Furthermore, children remaining in the lowest tertile of weight from birth to 6 months had a much higher risk of having low BMD at the whole‐body site at 6 months of age.…”
Section: Growth and Skeletal Developmentmentioning
confidence: 99%